Industrialisasi Berbasis Pertanian sebagai Grand Stratedy Pembangunan Ekonomi Nasional - Pantjar Simatupang; Nizwar Syafa'at (Forum penelitian Agro Ekonomi, 2000)
EnglishAs a developing economy Indonesia, should have a comprehensive integrated long-term development plan which may be used as the guideline in implementing its national economic development as well as an instrument for evaluating government accountability and credibility. The New Order regime had prepared its first and second long-term development plan for 1969-1993 and 1993-2018 successively. The twin plans, however, has led Indonesia to the 1997-1999 multi dimensions crises and is considered in appropriate in the existing new era of total reformation. It must be totally reconstructed. For this, public discussions on the need for the government to formulated the new grand strategy of national development have emerged, but up and down, in the last two years. As an active contribution to the public debase, this paper reviews previous, Indonesia development plans, others' countries experiences as well as grand theories of economic development. Then it is suggested that the agricultural based industrialization may be the most suitable one for Indonesia. The new grand strategy should be decided based on a national concensus in order to avoid the practice of just for political rhetoric's as was during the New Order regime. IndonesianBagi negara berkembang seperti indonesia, rencana pembangunan jangka panjang komprehensif-integratif sangat di perlukan sebagai acuan pelaksanaan pembangunan dan sebagai salah satu instrumen akuntabilitas dan kredibilitas pemerintah. Pemerintahaan Orde Baru telah menyusun rancangan pembangunan jangka panjang tahap I dan II masing-masing untuk peiode 1969-1993 dan 1993-2018. Rencana jangka panjang yang disusun rejim Orde Baru tersebut terbukti membawa Indonesia kedalam krisis tahun 1997-1999 dan sudah tidak sesuai dalam era Reformasi sehingga perlu dirancang ulang. Dalam dua tahun terakhir sesungguhnya telah muncul wacana publik yang menuntut agar pemerintah segera menyusun grand strategy ( strategi besar ) pembangunan nasional. Sebagai bagian dari wacana tersebut, tulisan ini mereview tentang konsepsi strategi pembangunan selama Orde Baru, pengalaman beberapa negara lain pemikiran teoritis tentang strategi pembangunan ekonomi. Berdasarkan hasil review tersebut, disarankan agar industrialisasi berbasis pertanian (agricultural based industrialization) dijadikan sebagai strategi besar (grand strategy) pembangunan nasional. Strategi tersebut haruslah dijadikan sebagai konsensus nasional, sehingga tidak sekedar retorika politik seperti pada masa Orde Baru.